2010
DOI: 10.3109/07357901003630967
|View full text |Cite
|
Sign up to set email alerts
|

Can hsp90α-Targeted siRNA Combined With TMZ Be a Future Therapy for Glioma?

Abstract: Hsp90alpha's vital role in cell cycle progression and apoptosis together with its presence in gliomas and absence in normal tissue, make it a credible target for cancer therapy. Three sets of dsRNA oligos designed to align different regions of the hsp90alpha sequence were used to downregulate hsp90alpha. SiRNA 1, 2, and 3 resulted in significant levels of silencing of hsp90alpha after 48 hr treatment (p < .0001). Concurrent treatment of the glioma cell line U87-MG with siRNA 1 and temozolomide (TMZ) resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Each protein band was normalized to the expression level of β-actin used as loading control, and the ratios are given by the numbers combined siRNA and drug treatment reduced the viability as did drug treatment alone. In contrast, combined siRNA against Hsp90α and temozolomide treatment led to a more pronounced reduction of viability of U87-MG glioma cells compared with drug treatment alone [4], which suggests that the effect of Hsp90α knock down might depend on cell line and drug used.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Each protein band was normalized to the expression level of β-actin used as loading control, and the ratios are given by the numbers combined siRNA and drug treatment reduced the viability as did drug treatment alone. In contrast, combined siRNA against Hsp90α and temozolomide treatment led to a more pronounced reduction of viability of U87-MG glioma cells compared with drug treatment alone [4], which suggests that the effect of Hsp90α knock down might depend on cell line and drug used.…”
Section: Discussionmentioning
confidence: 52%
“…SiRNA-mediated knockdown of several promising targets for cancer treatment (osteopontin, survivin, HIF-1α, aurora-A, Akt) has been already shown in the literature [7,14,17,19,20]. For example, the combination of siRNA against Hsp90α and temozolomide enhanced the sensitivity of glioma cells to this drug, suggesting a promising alternative treatment to chemotherapy alone [4]. In addition, clinical studies using this novel approach for cancer therapy have been already initiated [9].…”
mentioning
confidence: 99%
“…28 Furthermore, HSP90-α has therapeutic implications since both HSP90-α gene silencing and protein inhibitor approaches resulted in a dramatic reduction in cell viability of gliomas. 6,27 Alvespimycin (17-DMAG), an HSP90 inhibitor, is currently in clinical trials for several tumors with favorable results. 14,18 In studying MBs, Ayrault et al reported that, in order for 17-DMAG to exert its antitumorigenic effect, an intact p53 response is required.…”
mentioning
confidence: 99%
“…RNAi with non-enzymatic targets was also observed to be valuable in sensitizing cells to TMZ: In a previous study, it was noted that silencing the voltage-gated potassium channel Eag1 makes glioblastoma cells more vulnerable to TMZ (71). The same effect occurred for drug resistance proteins, heat-shock proteins 90, 27 and 72, and other targets involved in cell signaling (72)(73)(74)(75)(76)(77).…”
Section: Discussionmentioning
confidence: 98%